Comprehensive assessment of second-generation oak hybrids of S. S. Piatnytsky’s selection in Kharkiv region - Лось , С. А.; Сидоренко , С. В.; Григорьєва , В. Г. (Forestry and Forest Melioration, 2022)
Introduction Work on oak interspecies hybridization was actively carried out in the 30s and 40s of the 20th century. The hybrids were obtained in the USA and European countries. In Ukraine, such works were carried out by O. I. Kolesnikov, A. P. Yermolenko and S. S. Piatnytsky. After the 1940s, breeding programmes for interspecies hybridization of oaks in Europe and the USA ceased. The resulting interspecies hybrids were mostly kept in the arboretum’s collections and have been used in landscaping as decorative plants only. However, such research is the only from a couple of phases of the ongoing long-term project at Cornell University’s Urban Horticulture Institute whose aim is to select the best urban hybrid oak varieties for their future introduction into landscaping. The purpose of the oak hybridization carried out by S. S. Piatnytsky was to obtain drought-resistant forms suitable for creating stands in the harsh conditions of the Forest-Steppe and Steppe, in particular for shelterbelts and windbreaks. It was supposed to collect the acorns from free pollination of the first-generation (F1) hybrids using them further for planting F2 and F3 hybrid populations. To check the genetic properties of such populations, the test plots with hybrid progenies had been created in different regions of Ukraine. The four most promising hybrids were determined; their mother component was the large-pollinated oak of Caucasian origin. In 1993, these hybrids were included in the State Register of Plant Varieties of Ukraine. The paper involves the findings on the growth and development of 71-year-old hybrid oaks of S. S. Piatnytsky progenies, planted in shelterbelt 65a on the territory of the Dokuchaevske educational farm of the Kharkiv Agrarian University named after V. V. Dokuchaev (now Kharkiv State Biotechnology University). The aim of the research was to assess the oak hybrids of the S. S. Piatnytsky selection by progeny based on the assessment of the second generation according to a set of indicators. Materials and Methods Shelterbelt 65a was created by planting one-year-old oak hybrid seedlings, which were grown from the acorns obtained as a result of directed crosses and free pollination of the first generation of the best S. S. Piatnytsky oak hybrids. An English oak pollinated with a mixture of pollen of four species, planted in the outer row was used as a control. The condition of the trees was assessed according to a modified scale of the categories of oak viability and health condition. A comprehensive evaluation of variants was carried out on the basis of point evaluation of growth intensity, condition, quality of trunks and reproductive development. The average indicators of the variants were compared with the control to evaluate the growth intensity. We selected the trees candidates for the plus ones based on a set of features of the growth intensity condition and straightness of the trunk. It was done in accordance with generally accepted forestry requirements. Results All variants, without exception, were significantly inferior to the control in height. At the same time, the variant from pollination of Q. macranthera with unknown pollen was significantly superior to the control in diameter. The offsprings of Q. Timiryazevii and Q. Michurinii were significantly inferior to the control, and the variants Q. macranthera ? pollen mixture of four species and Q. macranthera ? Q. macrocarpa + Q. borealis were similar in these indicators to the control. The coefficient of variation in height within variants made 5.2–22.3%, and between variants, it was 4.5%. Variability in diameter within variants was higher and made 14.9–25.2%, between variants – 22.2%, respectively. The condition of the variants has mostly been satisfactory. In the shelterbelt, there are trees with various degrees of damage by surface fire. However, despite that, the trees resumed their growth and maintained a satisfactory condition. The comprehensive assessment showed that the examined hybrids scored from 9 (Q. macranthera ? unknown pollinator) to 12 points (Q. Timiriasevii, Q. macranthera ? a mixture of pollen of four species and Q. macranthera ? Q. macrocarpa + Q. borealis) . At that, the control scored 10 points. This indicates the relative prospects of the studied hybrids for forest creation and their prospects for being used in the protective stands in the region. In order to provide seeds for promising hybrids and to implement next stages of the selection process in the best variants, we selected trees - candidates for the plus ones. The diameter of almost all the selected trees exceeded the average indicators of the variants. The excess ranged from 1.2 to 71.2%, by height – from 1.0 to 19.2%. Conclusions At the age of 71, all examined F2 hybrids were significantly inferior to the control in height (15.4–25.0%). The average diameter of the hybrid from pollination of Q. macranthera with unknown pollen significantly exceeded the control (by 27.0%). The rest of the progenies were inferior to the control by 12.1–27.1%. According to the selection structure, the variant Q. macranthera ? unknown pollinator and the control, which did not have straight-stemmed trees, turned out to be the worst. In the rest of the variants, the share of straight-stemmed trees was from 20.6 to 36.4%. The comprehensive assessment proved the relative promisingness of S. S. Piatnytsky’s oak hybrids for creating forest stands and their promising potential for creating protective plantings in the Left-Bank Forest-Steppe and the Right-Bank Steppe conditions of Ukraine. The 11 trees selected in the best variants – candidates for the plus ones – were distinguished by their good condition and straight trunks. All selected trees correspond to the second selection category. To conclude, we recommend propagating them vegetatively and establishing a clonal seed orchard to obtain improved seeds. 4 Figs., 3 Tables, 19 Refs.